POLYMORPHISM OF ANGIOTENSIN II ALFA-GENE OF THE 1ST TYPE IN CHILDREN WITH SECONDARY HYPERTENSION - L. I. Kolesnikova; V. V. Dolgikh; T. A. Astakhova; V. V. Albot; E. V. Belyaeva (Acta Biomedica Scientifica)
The article presents the results of genetic typing of blood samples of children with glomerulonephritis and congenital abnormalities of the urinary system with different levels of blood pressure by A1166C-polymorphism of gene AGTR1 by the method of polymerase chain reaction. Comparative frequency analysis of genotypes (χ2 = 3,74; df = 5; p = 0,39) and alleles degrees of incidence (χ2 = 4,28; df = 5; p = 0,31) did not reveal statistically significant differences. Consequently, association of this polymorphism with secondary hypertension wasn't detected.